Ancient Observation of Spinal Cord Injury: The Case of the Assyrian Lion - Luvizutto, Gustavo J. (2018)
The description of paraplegia is considered a milestone in the history of neurology. The Egyptians provided excellent descriptions of spinal cord injuries, the Bible has several references to paraplegia, and, more recently, the pioneers of neurology described the classic syndromes related to spinal injuries and paraplegia. Here, we describe an ancient observation by the Assyrian people of paraplegia in an animal. In ancient Assyria, lion hunting was a ritualized activity conducted for political and religious purposes. The Lion Hunt of Ashurbanipal, a series of Assyrian palace reliefs from the North Palace at Nineveh dating from approximately 645 BCE, which is now in the British Museum in London, UK, shows King Ashurbanipal hunting lions. Applying modern knowledge of mammalian dermatomes to the images, we reveal a detailed and precise observation of paraplegia after spinal cord injury.